STRATEGI PERCEPATAN DALAM PENURUNAN STUNTING DI PERDESAAN MELALUI OPTIMALISASI DASHAT (STUDI KASUS CEGAH STUNTING) - Kembauw, Esther; Mailoa, Meitycorfrida; Ubro, Mincie H. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2025)
Stunting remains a strategic issue in human resource development in Indonesia, especially in rural areas with limited access to nutrition, health, and sanitation services. Through the Healthy Kitchen to Overcome Stunting (DASHAT) Program, the government seeks to optimize community empowerment in meeting family nutritional needs based on local foods. This community service article aims to describe strategies to accelerate stunting reduction through the optimization of DASHAT implementation as a form of cross-sector collaboration in promoting nutritional and health security in rural communities. Activities were carried out through a participatory and educational approach involving the community, posyandu cadres, and health workers, with a focus on increasing nutritional knowledge, healthy food processing, and strengthening the role of families in preventing stunting. The results of the community service show that optimizing the DASHAT program can increase community understanding of balanced nutrition, expand the use of local food ingredients, and strengthen clean and healthy living behaviors (PHBS). The implementation of the program also encourages the formation of a collaborative network between local governments, the private sector, and the community in accelerating the sustainable reduction of stunting. Thus, the strategy to accelerate the reduction of stunting through the optimization of DASHAT is effective in increasing awareness, participation, and family resilience to chronic nutritional risks in children under five in rural areas.